Porous CuCo2O4 Nanotubules for Li‐Ion Battery Anode. Issue 10 (4th April 2017) - Bhardwaj, Monika; Patrike, Apurva; Naphade, Rounak; Tonda, Surendar; Gawli, Yogesh; Ogale, Satishchandra
Abstract: We have used very simple and innovative electrospinning method for the preparation of CuCo2 O4 nanotubules interconnected with tiny CCO nanoparticles. The as‐prepared nanotubules render a very impressive performance and good stability without any template or composite such as CNT or graphene. 1D nanotubules showed reversible capacity of 767 mAh g ‐1 at a current density of 0.375 C and stability tested up to 360 cycles.Rate performance were done at different current densities i.e. 0.625 C, 1.25 C, 2.5 C and 0.375 C. Interestingly, it is noticed that CCO nanotubules are grown without any template or involvement of a second material as composite partner, and still shows a fairly impressive capacity of 553 mAh g ‐1 at a current rate of 1.25 C. Abstract : CuCo2 O4 nanotubules synthesized by electrospinning method show reversible capacity of 767 mAh g ‐1 at 0.375 C with good stability tested up to 360 cycles. At a current density of 1.25 C, a fairly impressive capacity of 553 mAh g ‐1 is seen during rate performance analysis.